Anthropometric adjustments are helpful in the interpretation of BMD and BMC Z-scores of pediatric patients with Prader-Willi syndrome. Issue 12 (December 2016) - Hangartner, T.; Short, D.; Eldar-Geva, T.; Hirsch, H.; Tiomkin, M.; Zimran, A.; Gross-Tsur, V.
Abstract Summary Anthropometric adjustments of bone measurements are necessary in Prader-Willi syndrome patients to correctly assess the bone status of these patients. This enables physicians to get a more accurate diagnosis of normal versus abnormal bone, allow for early and effective intervention, and achieve better therapeutic results. Introduction Bone mineral density (BMD) is decreased in patients with Prader-Willi syndrome (PWS). Because of largely abnormal body height and weight, traditional BMD Z-scores may not provide accurate information in this patient group. The goal of the study was to assess a cohort of individuals with PWS and characterize the development of low bone density based on two adjustment models applied to a dataset of BMD and bone mineral content (BMC) from dual-energy X-ray absorptiometry (DXA) measurements. Methods Fifty-four individuals, aged 5–20 years with genetically confirmed PWS, underwent DXA scans of spine and hip. Thirty-one of them also underwent total body scans. Standard Z-scores were calculated for BMD and BMC of spine and total hip based on race, sex, and age for all patients, as well as of whole body and whole-body less head for those patients with total-body scans. Additional Z-scores were generated based on anthropometric adjustments using weight, height, and percentage body fat and a second model using only weight and height in addition to race, sex, and age. Results As many PWS patients have abnormal anthropometrics, addition of explanatory variables weight, height, and fat resulted in different bone classifications for many patients. Thus, 25–70 % of overweight patients, previously diagnosed as normal, were subsequently diagnosed as below normal, and 40–60 % of patients with below-normal body height changed from below normal to normal depending on bone parameter. Conclusions This is the first study to include anthropometric adjustments into the interpretation of BMD and BMC in children and adolescents with PWS. This enables physicians to get a more accurate diagnosis of normal versus abnormal BMD and BMC and allows for early and effective intervention.